Desenvolvimento e aplicação de solventes eutéticos naturais profundos (NADES) para a extração de compostos bioativos da pitaya (Hyloreceus costaricensis) - PIRES, Ianê Valente (Universidade Federal do Pará, 2024)
NADES (Natural Deep Eutectic Solvents) have been highlighted as an alternative to traditional solvents in the fields of green chemistry. They consist of a mixture of two or more components with specific properties that form a liquid at room temperature, and their main advantages are high biodegradability, low cost and non-toxic factors. In this research, lactic acid, glycine, ammonium acetate, sodium acetate, and choline chloride were studied to obtain NADES, which were prepared with and without the addition of water. The NADES synthetized in aqueous médium, showed lower viscosities and densities, but there was no difference in the vibrating modes in the FTIR and Raman spectra when compared to those prepared without water addition. NADES synthesis has been confirmed by two different techniques, FITIR and Raman spectra, by targeting hydrogen bonds formation. Because of its notoriety in the market and in the scientific field, the pitaya (Hyloreceus Costaricensis) was used for the extraction study with NADES. The best results for bioactive compounds extraction (193.18 and 186.08 mg 100g-1 b.s) were found, respectively, in NADES formed by lactic acid with glycine and lactic acid with ammonium acetate, both with water addition.